Differentiated thyroid cancer: A retrospective evaluation of the impact of changes to disease management guidelines on patients in South East Scotland. Issue 2 (April 2019) - Williamson, A.G.; Wilmot, V.; Ntala, C.; Gibb, F.W.; Conn, B.; Nixon, I.J.
Abstract: Background: The British Thyroid Association (BTA) updated guidelines for the management of differentiated thyroid cancer (DTC) in 2014. A key update was that patients with unifocal disease >10–≤40 mm in diameter, aged <45 years and with no other risk factors could be considered for lobectomy alone. The aim of this study was to retrospectively evaluate the potential impact of these changes on the management of DTC in South East Scotland, and to analyse the characteristics of lobes now potentially considered for observation rather than resection. Methods: Consecutive patients were identified through prospectively held regional MDT minutes from 2009 to 13. Data included age, pT, pN, M stage, tumour size, vascular invasion and extra-thyroidal extension. Results: From a cohort of 281 patients, 22 (8%) could now be considered for lobectomy alone. Of these, 4 had disease in the contralateral lobe (18%), all of which were low-risk tumours with no influence on recommendation for radioactive remnant ablation (RRA). Analysis of all patients, regardless of age, with pT1-2N0M0 disease (n = 50) revealed 11 (22%) had contralateral disease. The presence of index multifocal disease was predictive of disease in the contralateral lobe. One patient (2%) had a finding in the contralateral lobe which may potentially influence the recommendation for RRA. In no cases did findings in the contralateral lobe elevate a patient to a group where RRA was routinely recommended by BTA guidelines. Discussion: The updated BTA guidelines are likely to affect only 8% of our cohort. Further analysis questions the role of age in excluding patients from a conservative approach. Highlights: The British Thyroid Association updated guidance for the management of differentiated thyroid cancer in 2014. Selected cases can now be considered for more conservative management. In South East Scotland, 8% of patients could now be considered for lobectomy alone. Further analysis questions the role of age in excluding patients from conservative management.